Awareness and Willingness of Blood Donation Among Medical Students of Nishtar Medical University, Multan, Pakistan: A Cross‐Sectional Descriptive Study - Areeba Zeb; Fatima Iftikhar; Amna Irshad; Muhammad Faiz Shujra; Amna Naseer; Amna Khalid; Elaf Eman; Sumia Fatima; Muhammad Farhan Jamil; Muddassir Khalid; Fred Segawa (Health Science Reports, 2026)
ABSTRACT Background Blood is a major component of emergency medical care. The blood transfusion plays a crucial role in saving lives and improving the quality of life. This study aims to assess the medical students’ awareness and willingness regarding voluntary blood donation at Nishtar Medical University, Multan, Pakistan. Methods This cross‐sectional study used the convenience sampling method to survey medical students at Nishtar Medical University between May and August 2025. A 48‐item self‐administered questionnaire with four sections—demographics, knowledge, attitude and practice—was used. Tests used in the analysis were the chi‐square, independent sample t ‐test and one‐way ANOVA test. Results A survey of 316 medical students showed a gender distribution of 57.3% females and 42.7% males. Good knowledge of voluntary blood donation (VBD) was found in 110 participants, with only 21.8% aware of the recommended donation frequency. Knowledge varied on donation volume (73.4%), process duration (50.3%), minimum age (16.8%), and weight requirements (41.8%). Only 25.3% knew when postpartum mothers could donate. School was the primary information source (58%). Positive attitudes prevailed, with 72.2% displaying good attitudes, regardless of demographics. However, 81.1% had never donated blood, mainly due to health issues (39.9%) or lack of reasons (32.4%). Conclusion The sampled medical students had good knowledge and a good attitude towards VBD, but there was a lack of practice in blood donation. Adequate awareness campaigns are required to increase awareness about voluntary blood donation, which is globally and locally an important healthcare subject.